Time to think on danger of Mobile Phone Radiation: Some evidences to support! - Kumar Patel, Vishnu; Patel, Umesh; Prasad Patel, Narmada (International Journal of Medical Research and Review, 2014)
Mobile phone use has increased dramatically since its introduction in 1980’s. The expanding use of this technology has been accompanied by concerns about health. Recently several expert groups critically reviewed the evidence on health effects of low-level exposure to radiofrequency (RF) electromagnetic fields.12 years back in October 2002, German physicians appealed to persons in the field of health care, politicians and the public with "great concern" claiming "soaring incidences of symptoms and diseases in the general population" to be causally related to the "commence of radio (wave) burden", i.e. due to mobile radio technology. Today his “great concern” has proved by many animal and human studies.